Genetic Variation Of Sry Gene In Yak And Related Bovines - K.P. RAMESHA,; S. JAYAKUMAR,; SANDEEP DAS,; T.K. BISWAS,; G.KRISHNAN,; V.S. CHOUHAN,; M.A. KATAKTALWARE, (International Journal of Pharma and Bio Sciences, 2012)
Y-chromosome markers have high value for the reconstruction of the male’s genetic and phylogeographic history. Genetic polymorphism and diversity of SRY gene in yak (Bos grunniens), yak hybrids and hill cattle of Arunachal Pradesh was investigated in the present study. Polymerase chain reaction and direct DNA sequencing was performed to find out the nucleotide differences between the species. The results of the multiple sequence alignment revealed that there exists variation at different positions viz., 61, 122 and 197.